2018
DOI: 10.1007/s10661-018-6599-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate uptake in an agricultural stream estimated from high-frequency, in-situ sensors

Abstract: Real-time, continuous, in situ water quality sensors were deployed on a fourth-order Iowa (U.S.) stream draining an agricultural watershed to evaluate key in-stream processes affecting concentrations of nitrate during a 24-day late summer (Aug-Sep) period. Overall, nitrate-nitrogen (NO-N) concentrations declined 0.11 mg L km, or about 1.9% km and 35% in total across 18 km. We also calculated stream metabolic rates using in situ dissolved oxygen data and determined stream biotic N demand to be 108-117 mg m day.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…If assimilation driven by photosynthetic N uptake is a principal driver of diel NO 3 − patterns, then minima should occur during daylight and maxima during darkness. Many studies show such a diel pattern with peaks during evening to early morning and minima during afternoon to early evening (Cohen, Heffernan, Albertin, & Martin, ; Heffernan & Cohen, ; C. S. Jones et al, ; Pellerin et al, ; Rode et al, ). However, peak diel NO 3 − closer to the middle of the day is often observed when photosynthetic demand should be high (Burns et al, ; Duncan et al, ; Halliday et al, ; Rusjan & Mikoš, ).…”
Section: In‐stream and Near‐stream Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…If assimilation driven by photosynthetic N uptake is a principal driver of diel NO 3 − patterns, then minima should occur during daylight and maxima during darkness. Many studies show such a diel pattern with peaks during evening to early morning and minima during afternoon to early evening (Cohen, Heffernan, Albertin, & Martin, ; Heffernan & Cohen, ; C. S. Jones et al, ; Pellerin et al, ; Rode et al, ). However, peak diel NO 3 − closer to the middle of the day is often observed when photosynthetic demand should be high (Burns et al, ; Duncan et al, ; Halliday et al, ; Rusjan & Mikoš, ).…”
Section: In‐stream and Near‐stream Processesmentioning
confidence: 99%
“…Such insights are readily derived from comprehensive storm‐by‐storm c – Q analyses. As sensor records extend over increasingly longer periods, event‐based and composite c – Q analysis approaches can be compared, thus eliminating the possibility that differences in interpretation may have resulted from low sampling frequency and inadequate representation of variation with discharge and season (Duncan, Welty, et al, ; C. S. Jones, Kim, Wilton, Schilling, & Davis, ).…”
Section: Concentration–discharge Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Koenig, Shattuck, Snyder, Potter, and McDowell (2017) Questions still remain about the relationship between nutrients and in-stream processing in anthropogenic systems. High-temporal sensors have been used to evaluate N patterns in agricultural streams, with low concentrations observed in the afternoon and high concentrations in the early morning due to higher assimilation during photosynthesis than denitrification at night (Jones, Kim, Wilton, Schilling, & Davis, 2018). High frequency logging has shown that variations in anthropogenic inputs can overprint diel N patterns, which can make predictions of load from grab samples uncertain (Carey, Wollheim, Mulukutla, & Mineau, 2014;Duan, Powell, & Bianchi, 2014;Pellerin et al, 2009).…”
Section: High-temporal Sensors and The Impact On Understanding Nutrmentioning
confidence: 99%